2012
DOI: 10.1095/biolreprod.112.104208
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis of a Deep Mouse Epididymal Sperm Proteome1

Abstract: Spermatozoa are highly specialized cells that, when mature, are capable of navigating the female reproductive tract and fertilizing an oocyte. The sperm cell is thought to be largely quiescent in terms of transcriptional and translational activity. As a result, once it has left the male reproductive tract, the sperm cell is essentially operating with a static population of proteins. It therefore is theoretically possible to understand the protein networks contained in a sperm cell and to deduce its cellular fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 51 publications
2
42
1
Order By: Relevance
“…While suggestive of protein biosynthesis and consistent with observations by Chauvin et al . () on an mRNA translational apparatus in spermatozoa, neither their nor our observations warrant as yet a paradigm shift. This will await the conclusive demonstration of in situ mRNA translation by polysomes of sperm‐specific proteins as predicted in our study (Au et al ., 2015a).…”
Section: Proteins Categorized In the Protein Synthesis And Folding Cacontrasting
confidence: 70%
See 1 more Smart Citation
“…While suggestive of protein biosynthesis and consistent with observations by Chauvin et al . () on an mRNA translational apparatus in spermatozoa, neither their nor our observations warrant as yet a paradigm shift. This will await the conclusive demonstration of in situ mRNA translation by polysomes of sperm‐specific proteins as predicted in our study (Au et al ., 2015a).…”
Section: Proteins Categorized In the Protein Synthesis And Folding Cacontrasting
confidence: 70%
“…Previous proteomics studies on whole spermatozoa (Chauvin et al ., ; Chocu et al ., ; Baker et al ., ) uncovered GLUT‐3 and other glycolytic metabolic enzymes as prominent. In humans, 436 of the 1056 proteins found in spermatozoa belonged to various metabolic pathways, with glycolytic proteins being the highest expressed (Baker & Aitken, ).…”
Section: Sweeting Up the Spermatozoa By Glycolysismentioning
confidence: 98%
“…A survey of these 234 proteins revealed that 92.3% and 94.4% of these proteins were also identified in our RJF SF datasets, respectively. We then asked if these predicated sperm proteins identified in our SF dataset represent evolutionary conserved sperm components present in human41 and mouse42 sperm. Of the sperm proteins present in our dataset, 81 (74%) and 68 (62%) were also present in the human and mouse sperm proteomes, respectively, further supporting the potential importance of these proteins in sperm maturation and function.…”
Section: Resultsmentioning
confidence: 99%
“…The same analysis pipeline was used to reanalyze available raw MS/MS data from fractionated domestic chicken SF samples24. SF proteomes were compared to the chicken blood plasma proteome36, the exosome ExoCarta high quality protein marker dataset47, human blood plasma37, human sperm41, mouse epididymal sperm42 and human seminal plasma35 using orthology relationships in Ensembl Genes 84 (Galgal4). Composition of protein datasets were analyzed using the DAVID Bioinformatics Resource (6.7)8081, including statistical analyses of functional enrichment using the G. gallus genome as the background dataset for comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Results from proteomic studies can provide overview information on the protein expression of gametes and facilitate studies on gene function, evolution, and therapy etc. (Tops et al 2010;Chauvin et al 2012;Rettie & Dorus 2012;Bayasula et al 2013;McReynolds et al 2014). In C. gigas, two preliminary proteomic studies have been conducted to identify proteins associated with oocyte quality and spermatogenesis (Corporeau et al 2012;Kingtong et al 2013).…”
Section: Introductionmentioning
confidence: 99%